ANALYSIS OF THE EFFECT OF CARBON TAX ON FOSSIL FUELS AND RENEWABLE ENERGY IN EUROPEAN COUNTRIES IN THE PERIOD 1996 "“ 2022 - Satriawan adinugroho -; Diana - Airawaty (Journal of Applied Accounting and Taxation, 2024)
This study aims to analyze the impact of carbon tax implementation on fossil fuel consumption and renewable energy development in European countries over the period 1996-2022. The increasing use of fossil fuels has become a global issue as their carbon emissions trigger climate change and other negative impacts. As a solution, renewable energy is seen as a cleaner and more environmentally friendly alternative. A carbon tax is implemented as one policy to encourage the transition to renewable energy by imposing a surcharge on fossil fuels based on the amount of carbon emissions produced. This study uses panel data to measure the effect of carbon tax on fossil fuel consumption and renewable energy use in European countries in the period 1996 - 2022. The results of the analysis show that the implementation of carbon tax has no significant effect on fossil fuel use but can increase the use of renewable energy in the sample countries. The findings provide important insights for Indonesian policymakers in designing carbon tax policies to support a more sustainable energy transformation.